Physio-biochemical responses of hybrid citrus rootstock progenies to NaCl induced salinity - KALAL, PRASHANT; SHARMA, R M; DUBEY, A K; KAMIL, DEEBA; LEKSHMY, S; KUMAR, AMRENDER; AWASTHI, O P (The Indian Journal of Agricultural Sciences, 2019)
The study consisted 30 hybrids of Pummelo (P) × Troyer (T) with two check cultivars, viz. Attani-2 and Troyer citrange, were subjected to 100 mM NaCl treatment through irrigations till the appearance of foliar symptoms. Of the 30 hybrids, only 3 hybrids, viz. P × T-86, P × T-98 and P × T -102 showed higher photosynthetic rate (A) (6.22 -6.42 μmol m2/s) than other hybrids. Furthermore, the level of O2 - was lowest in Attani-2. The lowest Cl- content was noticed in P × T-102 (0.03%) followed by P × T-98 (0.04%). Of the 30 hybrids (Pummelo × Troyer citrange), evaluated against 100 mM NaCl induced salinity, 3 hybrids P × T-86, P × T-98 and P × T-102 had very low scorching of leaves (32.88-33.15%), and were found tolerant as these hybrids expressed the low level of lipid peroxidation and Cl- accumulation in leaves, besides maintaining the higher A and MSI than other hybrids and Troyer citrange.